Abiotic stresses in rice production: Impacts and management - Pathak, Himanshu; Kumar, Mahesh; Molla, Kutubuddin A; Chakraborty, Koushik (ORYZA-An International Journal of Rice, 2021)
Rice, a key staple food crop in the world and India, offers food and nutrition security to millions of the global population. Abiotic (water, soil, atmospheric) stresses affect yield and quality of rice. This necessitates stressresilientrice production technologies sufficiently fortified by novel stress mitigation and adaptation strategies. Recent crop improvement strategy has partially managed to resolve the challenges presented by abiotic stresses such as high temperature, drought, salinity, alkalinity, waterlogging and mineral deficiency. The complication and multiplicity of abiotic stresses necessitate the use of extensive, integrative and multi-disciplinary techniques to achieve resilience. Crop improvement, along with the agronomic interventions, is essential to stabilise the productivity and profitability of rice production. This article gives an overview of the potential impacts of abiotic stress on rice and suggests the adaptation and mitigation strategies.